Development of tsunami early warning systems and future challenges - J. Wächter; A. Babeyko; J. Fleischer; R. Häner; M. Hammitzsch; A. Kloth; M. Lendholt (Natural Hazards and Earth System Sciences, 2012)
Fostered by and embedded in the general development of information and communications technology (ICT), the evolution of tsunami warning systems (TWS) shows a significant development from seismic-centred to multi-sensor system architectures using additional sensors (e.g. tide gauges and buoys) for the detection of tsunami waves in the ocean. Currently, the beginning implementation of regional tsunami warning infrastructures indicates a new phase in the development of TWS. A new generation of TWS should not only be able to realise multi-sensor monitoring for tsunami detection. Moreover, these systems have to be capable to form a collaborative communication infrastructure of distributed tsunami warning systems in order to implement regional, ocean-wide monitoring and warning strategies. In the context of the development of the German Indonesian Tsunami Early Warning System (GITEWS) and in the EU-funded FP6 project Distant Early Warning System (DEWS), a service platform for both sensor integration and warning dissemination has been newly developed and demonstrated. In particular, standards of the Open Geospatial Consortium (OGC) and the Organization for the Advancement of Structured Information Standards (OASIS) have been successfully incorporated. In the FP7 project Collaborative, Complex and Critical Decision-Support in Evolving Crises (TRIDEC), new developments in ICT (e.g. complex event processing (CEP) and event-driven architecture (EDA)) are used to extend the existing platform to realise a component-based technology framework for building distributed tsunami warning systems.